Persepsi Saudara Muslim Terhadap Program Dakwah di Pertubuhan Kebajikan Islam Malaysia (PERKIM) Kebangsaan, Kuala Lumpur (Sains Humanika, 2014)
National Muslim Welfare Organization Malaysia (PERKIM), Kuala Lumpur is a non-government organization that plays a vital role in the effort of da’wah and taking care of the Muslim brothers’ welfare in Malaysia. Even though there are a lot of programs conducted by PERKIM in the attempt of enhancing the welfare of Muslim brothers, unfavourable perceptions are still heard saying that the programs are not giving big impact in improving Islamic practices among them as a whole. Therefore, this article discusses the findings related to the perceptions of Muslim brothers towards the da’wah programs carried out by National PERKIM, Kuala Lumpur. This research was held in National PERKIM, Kuala Lumpur involving 265 respondents among Muslim brothers who had took part in PERKIM’s da’wah programs. The research design is observational using the methods of observation, interview and survey. A pilot study had been carried out and the Alpha Cronbach value of this study shows that the reliablity of the test tool is high which is around 0.9. The research findings found that the respondents have a good perception towards programs conducted by PERKIM, where 52.8 percent of the respondents agree that contents of the programs are suitable with their level of understanding. 46.4 percent of the respondents strongly agree that the religion officers deliver the knowledge dedicatedly with clear and understandable manner. On the other hand, 43.8 percent respondents agree that time of the programs does not overlap with their daily activities and 45.7 percent of the respondents agree that the da’wah methods in PERKIM are relevant and giving the chance for Muslim brothers to enhance their religion knowledge in a better way.